Kebebasan Berserikat sebagai Prinsip Fundamental dalam Dinamika Hubungan Industrial di Indonesia - Ilham Firmansyah; Rizqy Rahmansyah; Cindy Gracella Hutabarat; Rismanro Simatupang; Julius Caesar Transon Simorangkir (DPPM Universitas Pelita Bangsa, 2026)
This study aims to analyze the implementation of the freedom of association as a fundamental right within industrial relations in Indonesia. It highlights the application of this right as guaranteed by the 1945 Constitution of the Republic of Indonesia, Law No. 13 of 2003 on Manpower, Law No. 21 of 2000 on Trade Unions/Labor Unions, and the ILO Convention No. 87 of 1948 on Freedom of Association and Protection of the Right to Organize. Using a normative juridical approach, this research examines the effectiveness of legal protection for workers against discriminatory practices such as union busting, which refers to systematic efforts by companies to obstruct the establishment or activities of labor unions. The results show that although the right to organize is legally guaranteed, its implementation remains weak due to inadequate law enforcement and unequal power relations between workers and employers. Therefore, stronger labor supervision, firm legal sanctions, and the empowerment of labor unions are required to realize fair and democratic industrial relations